KAJIAN HISTORIS DAN KULTURAL AMPARAN TATAK SEBAGAI KULINER TRADISIONAL KHAS SAMARINDA - Sarip, Muhammad; Hajati, Syifa; Harma, Winda Pramita (Badan Perencanaan Pembangunan Daerah, Penelitian dan Pengembangan Kota Samarinda, 2024)
Culinary is one of the works of human culture. In the city of Samarinda, whose population is heterogeneous, there is a snack that represents the culinary uniqueness of the capital of East Kalimantan. Amparan tatak, as a snack produced by the Banjar community in Samarinda, can be accepted as one of the iconic cuisines. This research aims to describe the historical dynamic of Samarinda from the colonial period to the present, then to describe the role of the Banjar entity in shaping the diverse culture of Samarinda’s society, and subsequently to describe the process by which amparan tatak snacks can become a distinctive culinary specialty of the city of Samarinda. In this study, the historical research method is used, which includes four procedures: heuristics, verification, interpretation, and historiography. The research results show that there was a relationship between the Banjar Kingdom and the Kutai Kingdom in the past, in this context Samarinda as the port city of Kutai. The existence of the Banjar community in Samarinda since the colonial era has significantly influenced the culture of Samarinda’s society. In the past, amparan tatak was sold in the city of Samarinda by walking around and always became a must-try culinary dish traditionally served during the breaking of the fast ritual in Ramadan. Based on this research, it is recommended that the Samarinda City Government manage the registration of amparan tatak as Indonesia’s Intangible Cultural Heritage.